Pulmonary Embolism in a Donor of Living Donor Liver Transplantation - Shinji Onda (Case Reports in Gastroenterology, 2019)
Pulmonary embolism (PE) is a rare but potentially fatal complication that may develop in a living liver donor. Here, we report a case of non-massive PE diagnosed by elevated serum D-dimer levels and successfully treated using anticoagulant therapy. A 57-year-old man underwent extended left hepatectomy as a living liver donor. His past medical history included hypertension and dyslipidemia which required medication and a history of smoking. Mechanical prophylactic measures for venous thromboembolism, including intermittent pneumatic compression and elastic stocking, were used; however, no pharmacological prophylaxis was used. Although the patient ambulated on postoperative day (POD) 1, he developed hypoxia. Serum D-dimer level was elevated to 29.3 ng/mL on POD 2. Enhanced computed tomography revealed small peripheral PEs in the branches of the right upper, right middle, and left lower lobes without deep vein thrombosis. Intravenous heparin was initiated followed by warfarin. The thrombi resolved completely by POD 13, following which warfarin was continued for 3 months. As of 25 months after donation, the patient remains well without recurrence of PE. Early diagnosis and treatment of postoperative PE are critical for preventing mortality of liver donors.